Peningkatan Kompetensi Kader Posyandu dalam Pengukuran Antropometri untuk Meningkatkan Kualitas Data Gizi Anak Makassar - Irma Nur Afiah; Rezky Putri Indarwati Abdullah; Andi Dwi Wahyuni (Svarga Pena : Jurnal Pengabdian Kepada Masyarakat, 2025)
Posyandu in Paropo Subdistrict, Makassar City, plays a crucial role in community health services, particularly in child growth monitoring. However, Posyandu cadres face challenges in applying proper anthropometric principles due to limited knowledge and skills in conducting static and dynamic anthropometric measurements. This condition affects the accuracy of children's weight and height data and leads to the lack of follow-up from local authorities in addressing nutritional issues. This Community Service Program (PKM) aims to enhance the competencies of Posyandu cadres in anthropometric measurements through ergonomics-based training. The evaluation results indicate a significant improvement in Posyandu cadres' understanding and skills in performing accurate anthropometric measurements. This competency enhancement contributes to better-quality anthropometric data, which can be utilized as a basis for child health policies. This program is expected to be sustainable with the support of local government to improve community health services.Keywords: Anthropometry, Posyandu cadres, ergonomics, static and dynamic measurement, child health.